Rating of Māori Land: A Legal History - Boast, Richard (Victoria University of Wellington Law Review, 2022)
This article deals with the rating of Māori freehold land as a case study of a field of law where Māori Land Law and Taxation Law overlap. Rates, are, of course, a type of tax. For Māori landowners, paying rates and rates debts were probably the most important tax-related problem they had to confront. The issue was not only that Māori landowners often could not afford to pay rates. While that was the case, the real issue was the overlay between Māori land law and tax law as such. The real problem with rating of Māori land was the Māori land law system itself. This article explains why this is so, and utilises rating law as a window into the complexities of the statutory Māori land law system and the complexities it caused to Māori landowners.